2020
DOI: 10.1111/ijcs.12565
|View full text |Cite
|
Sign up to set email alerts
|

Profiling consumers based on information use and trust in a developing economy

Abstract: In the wake of the intense debate about the effect of poultry imports on domestic poultry industries in sub‐Saharan Africa, information campaigns have evolved to encourage the consumption of domestic poultry meat products. Nevertheless, consumers use numerous channels to find information, and thus, the extent to which resources should be allocated to these channels to reach segments of consumers is vital. The purpose of this paper is to identify consumer groups based on use and trust in information sources and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…One representative study found that consumers can be segmented based on their use of and attitudes toward nutrition labels, and that such segmentation can provide valuable information for a targeted communication approach [14]. A few recent studies have identified consumer groups based on the use of and trust in information sources [15] and profiled the segments using sociodemographic variables [16], purchase motives [17], and consumption behavior [18]. To the best of our knowledge, our study is the first in which consumer segments based on nutrition information-seeking behaviors have been related to food consumption in China.…”
Section: Introductionmentioning
confidence: 99%
“…One representative study found that consumers can be segmented based on their use of and attitudes toward nutrition labels, and that such segmentation can provide valuable information for a targeted communication approach [14]. A few recent studies have identified consumer groups based on the use of and trust in information sources [15] and profiled the segments using sociodemographic variables [16], purchase motives [17], and consumption behavior [18]. To the best of our knowledge, our study is the first in which consumer segments based on nutrition information-seeking behaviors have been related to food consumption in China.…”
Section: Introductionmentioning
confidence: 99%